Bathyraja griseocauda, Graytail Skate - Pollom, R.; Dulvy, N. K.; Acuña, E.; Bustamante, C.; Chiaramonte, Gustavo Enrique; Cuevas, J. M.; Herman, K.; Paesch, L.; Pompert, J.; Velez Zuazo, X.
The Greytail Skate (Bathyraja griseocauda) is a large (to 157 cm total length) skate that occurs in the Southeast Pacific and Southwest Atlantic Oceans from Coquimbo, Chile south around Cape Horn and north to Uruguay, including the Falkland Islands (Malvinas), and is demersal on the mid-continental shelf and upper slope at depths of 30?1,010 m. It is captured in trawl and longline fisheries targeting skates, squid, shrimp, scallops, hake, and Patagonian Toothfish (Dissostichus eleginoides) that are inadequately managed and together operate throughout its range. Its large body size and relatively unproductive life history make it particularly vulnerable to overfishing. In the Southeast Pacific, this skate is captured and discarded dead in inadequately managed fisheries that operate throughout that portion of its range. In the Southwest Atlantic, where large skates are typically utilized or exported for human consumption, the catch-per-unit-effort (CPUE) for this skate in the Falkland Islands (Malvinas) multi-species skate fishery declined consistently and substantially from 120 to 23 kg/hr between 1994 and 2006, and increased to 70 kg/hr in 2013 due to a change in the area fished. Although no later data are available, this fishery continues and is still not managed at the species level. In Argentina, there are no species-specific data, but rays in general declined in CPUE in the 1990s and early 2000s. Overall, due to the level of inadequately managed fishing pressure it is exposed to across its range, its large size and relatively unproductive life history, the decline in CPUE of rays in general in some areas, and the noted decline in CPUE (although succeeded by an increase) of this species in the Falkland Islands, it is suspected that this skate has undergone a population reduction of 50?79% over the past three generations (69 years). Therefore, the Greytail Skate is assessed as Endangered A2bd. Fil: Pollom, R. University Fraser Simon; Canadá Fil: Dulvy, N. K. University Fraser Simon; Canadá Fil: Acuña, E. ...